Government Management in the Political Dynamics of Regional Head Elections: A Case Study in Indonesia - Saragih, Jopinus; Supriatna, Ucu (Universitas Negeri Makassar, 2024)
The political dynamics of regional head elections in Indonesia often intersect with government management practices, creating challenges and opportunities for effective governance. This study aims to explore how government management adapts to and is influenced by the political landscape during regional elections, particularly in terms of decision-making, resource allocation, and public service delivery. Using a qualitative research approach, data were collected through in-depth interviews with government officials, election committee members, and local political figures, complemented by document analysis of election regulations and policies. The findings reveal that political pressures significantly shape government management strategies, often leading to compromises in bureaucratic efficiency to meet electoral demands. Furthermore, the study highlights the role of political actors in influencing government priorities and resource distribution, emphasizing the need for institutional safeguards to maintain neutrality and professionalism in public administration. The results suggest that improving the transparency of government processes during election periods could mitigate political interference and enhance governance outcomes.